2016
DOI: 10.1371/journal.pone.0164416
|View full text |Cite
|
Sign up to set email alerts
|

Can CT Screening Give Rise to a Beneficial Stage Shift in Lung Cancer Patients? Systematic Review and Meta-Analysis

Abstract: ObjectivesTo portray the stage characteristics of lung cancers detected in CT screenings, and explore whether there’s universal stage superiority over other methods for various pathological types using available data worldwide in a meta-analysis approach.Materials and MethodsEMBASE and MEDLINE were searched for studies on lung cancer CT screening in natural populations through July 2015 without language or other filters. Twenty-four studies (8 trials and 16 cohorts) involving 1875 CT-detected lung cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…The high heterogeneity of cancer is another issue that has important implications for lung cancer screening. According to our recent meta-analysis [ 18 ], indolent cancers contributed to over-diagnosis, as they comprised a large proportion of cancers additionally detected with LDCT. In addition, no evidence of superiority with LDCT for the early detection of small cell lung cancers was observed, unlike non-small cell lung cancers.…”
Section: Study Area 2: Precise Screening With Insights From Molecularmentioning
confidence: 99%
“…The high heterogeneity of cancer is another issue that has important implications for lung cancer screening. According to our recent meta-analysis [ 18 ], indolent cancers contributed to over-diagnosis, as they comprised a large proportion of cancers additionally detected with LDCT. In addition, no evidence of superiority with LDCT for the early detection of small cell lung cancers was observed, unlike non-small cell lung cancers.…”
Section: Study Area 2: Precise Screening With Insights From Molecularmentioning
confidence: 99%
“…A kisebb vizsgálatok összesített eredménye nem mutatott ki szignifikáns mortalitáscsökkenést az LDCT-vel szűrt karon, a legnagyobb randomizált, kontrollcsoportos vizsgálat viszont 20%-os relatívkockázat-csökkenésről számolt be. Wang és mtsai nyolc vizsgálatot válogattak be az elemzésükbe, amely az alacsony dózisú CT-vel történő szűrésnek a tüdőrák felfedezéskori stádiumára vonatkozó pozitív hatására szolgáltat bizonyítékot [10]. Az első stádiumban felfedezett tüdőrákok aránya 12,2%-kal volt magasabb az LDCT-vel szűrt betegek esetén a mellkasröntgenhez képest, és 46,5%-kal a nem szűrt betegekhez viszonyítva.…”
Section: Hatásosságunclassified
“…Több nagy, randomizált, kontrollcsoportos vizsgálat sem tudta igazolni, hogy a mellkas-röntgenfelvétellel való tüdőszűrés csökkentené a tüdőrákos mortalitást a nem szűrt csoporthoz képest [7,8]. Emellett nemrég publikált szisztematikus irodalomkutatás és metaanalízisek eredményei is azt bizonyít-ják, hogy a mellkasröntgennel végzett eljárás nem haté-kony módja a célzott tüdőrákszűrésnek [9,10]. Hiába csökken ugyanis a reszekábilis stádiumban felfedezett betegek aránya, ha eközben a kedvezőtlen tesztkarakterisztikák miatt a szűrési eljárás hatásossága alacsony és nem javul a betegek életesélye.…”
unclassified
“…1 Both the population lost to follow-up and the population of patients with an incomplete diagnosis had a smaller lesion size compared with the counterpart final inclusion population. A recent meta-analysis by Wang et al 3 identified temporal trends of a proportion regarding increased stage I lung cancer since the worldwide introduction of CT screening. In response to the anticipated temporal increases of CT screening since the approval for coverage by the Centers for Medicare and Medicaid Services in 2015, the proportion of early-stage cancer or nonmalignant cases in the United States is anticipated to increase.…”
Section: More Health Outcomes Analysis From More Representative Populmentioning
confidence: 99%